2023
DOI: 10.1098/rstb.2022.0340
|View full text |Cite
|
Sign up to set email alerts
|

Conserved features of eye movement related eardrum oscillations (EMREOs) across humans and monkeys

Stephanie N. Lovich,
Cynthia D. King,
David L. K. Murphy
et al.

Abstract: Auditory and visual information involve different coordinate systems, with auditory spatial cues anchored to the head and visual spatial cues anchored to the eyes. Information about eye movements is therefore critical for reconciling visual and auditory spatial signals. The recent discovery of eye movement-related eardrum oscillations (EMREOs) suggests that this process could begin as early as the auditory periphery. How this reconciliation might happen remains poorly understood. Because humans and monkeys bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Eye position effects in AC may become even stronger if subjects are also required to associate the information gained from eye position with auditory information. In these conditions, neuronal activity in AC may be affected by eye position signals through feedforward projections from the ear or inferior colliculus or feedback projections from frontal and parietal cortical regions [2–8,21–25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye position effects in AC may become even stronger if subjects are also required to associate the information gained from eye position with auditory information. In these conditions, neuronal activity in AC may be affected by eye position signals through feedforward projections from the ear or inferior colliculus or feedback projections from frontal and parietal cortical regions [2–8,21–25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in primates have demonstrated that the position of the eyes can affect the responses to sounds and the ongoing activity in the ear [1–3] and the inferior colliculus [4–8]. These findings indicate that in these stages of the auditory pathway, auditory information can be combined with information about the eye position and thus with the visual space in which eye position can be used as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Lovich et al. [ 18 ] extend this fascinating story, elucidating quantitative relationships between eardrum oscillations and saccade metrics in both humans and monkeys. They suggest that similarities and differences in these relationships across species will help guide generation of hypotheses about the functional role of this surprising phenomenon.…”
Section: Overview Of the Theme Issuementioning
confidence: 97%